(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
This paper aims to explain the effect of the taxes policy including direct & indirect taxes on supporting the domestic Investment in Iraq. This could help the official planners for drawing the future policies that help provoking (istumlating) the domestic investment in Iraq the quantitative analysis approach was adopted using regression model. The results showed the significance of the effects of both direct & indirect taxes policies on domestic as a simple correlation coefficient ( r ) of ( 0.6 ) , ( 0.64 ) respectively.